EFFICACY OF INTRAVENOUS ESMOLOL WITH INTRANASAL NITROGLYCERINE SPRAY GIVEN BEFORE ENDOTRACHEAL EXTUBATION ON THE ATTENUATION OF PRESSOR RESPONSE: A COMPARATIVE STUDY - Kokate, Minal V; Kokate, Vikram R; Mahure, Shirish M; Jumade, Prashil P (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to compare the effects of intravenous esmolol and intranasal nitroglycerine spray on attenuation of extubation pressor response in terms of hemodynamic parameters and to compare the adverse effects, if any, of either drug. Methods: This was a randomized comparative study conducted in a tertiary care medical college in which 64 patients of ASA Grade I with age between 18 and 60 years, including both males and females undergoing elective non cardiac surgeries under general anesthesia with orotracheal intubation were included in this study on the basis of a predefined inclusion and exclusion criteria. Patients were divided into two groups (Depending on whether they received Intravenous Esmolol or NTG spray) of 32 patients each. Attenuation of extubation pressor response in terms of hemodynamic parameters (systolic blood pressure [SBP], diastolic blood pressure [DBP], mean arterial pressure [MAP], heart rate, and rate pressure product) were recorded and compared before induction, during surgery and postoperatively up to 10 min after surgery. Results: The gender distribution was comparable in both the groups. The mean age of patients in Group A and Group B was found to be 36.90±10.12 and 35.20±11.32 years, respectively. The mean age of both the groups was found to be comparable with no statistically significant difference. Both the study groups were comparable in base line parameters with no significant difference seen in mean age, mean heart rate, mean SBP and DBP, MAP, anesthesia time, and surgery time. Both drugs controlled the blood pressure changes effectively; however, NTG group had a better control of systolic as well as DBP. Heart rate was better controlled in esmolol group. Conclusion: Intranasal nitro-glycerine and intravenous esmolol before tracheal extubation in ASA Grade I patients are simple, effective, and practical methods of blunting cardiovascular responses to tracheal extubation.